A Comparison of Regulatory Awareness and Green Supply Chain Management Practices Among Chinese and Japanese Manufacturers. (23rd March 2015) - Zhu, Qinghua; Qu, Ying; Geng, Yong; Fujita, Tsuyoshi
Abstract: Leading manufacturers in developed countries generally have high environmental awareness and implement proactive environmental management practices such as green supply chain management (GSCM). However, it is uncertain if smaller manufacturers in developed countries are more proactive than all manufacturers in developing countries. To understand this situation, we carried out surveys among small and medium‐sized Japanese manufacturers, leading Chinese manufacturers and traditional Chinese manufacturers. Statistical results show that leading Chinese manufacturers have the highest awareness of both domestic and international environmental regulations/policies, and implement all GSCM practices at the highest level. Leading Chinese manufacturers and Japanese manufacturers are aware of international environmental regulations/policies, but such awareness only motivates them to implement eco‐design practices. Traditional Chinese manufacturers have limited awareness of international environmental regulations/policies, but such awareness brings all types of GSCM practice. Such results can be helpful for different manufacturers in both developed and developing countries to develop suitable environmental strategies. Copyright © 2015 John Wiley & Sons, Ltd and ERP Environment